Role of Male effect on Reproductive Efficiency of Nulliparous Santa Inês and Morada Nova ewes raised in Different Regions - Filho, Fernando Tenório; Ferreira-Silva, José Carlos; Nascimento, Pábola Santos; Neto, Leopoldo Mayer de Freitas; Moura, Marcelo Tigre; Irmão, José Monteiro Almeida; Oliveira, Marcos Antonio Lemos (Acta Scientiae Veterinariae, 2016)
Background: The male effect is an attractive strategy to increase herd production by concentrating mating events and deliveries and further allowing the adoption of genetic improvement programs. It holds similar efficiency to those chemically based estrous synchronization methods, but has the advantage of being a natural method. The work was aimed to evaluate the influence of male effect on estrous induction and synchronization, pregnancy and prolificacy of nulliparous Santa Inês and Morada Nova ewes raised in Semiarid and Zona da Mata regions of Pernambuco state. Materials, Methods & Results: Santa Inês (n = 80) and Morada Nova (n = 80) females, with age from 11 to 12 months, after being evaluated and selected, were identified with plastic ear tags, weighted and maintained isolated from males, during 30 days before experiment onset, without any physical, visual, olfactive and auditive contact. Estrous events were observed twice a day (6:00 and 16:00 h) by trained personnel, during a breeding season of 60 days, and estrous were considered synchronized when detected, within first five days of breeding season. Rams of Santa Inês (n = 2) and Morada Nova (n = 2) breeds were selected based upon reproductive capacity by an andrology exam, and were marked on the externum bone region with a wax and ink (4:1) mixture, and were marked in female lots in order to identify females in estrous. After ten days of breeding season onset, rams were again marked with the same wax and ink mixture, but with a different ink color. Pregnancy diagnosis was performed on day 30 by ultrasonography and confirmed on day 60 after the last mating. The statistical analysis was performed using SAS, version 8. Differences of 5% (P < 0.05) or lower were considered significant. The results show that estrous synchronization in the semiarid region in both breeds was detected in 10% of females. The total pregnancy on first service was 45.00% and on second was 52.94%, with 85.18% of singleton and 14.81% twin deliveries, with prolificacy de 1.15 ± 0.38. In the Zona da Mata region 10% Santa Inês and 15% Morada Nova females had synchronized estrous (P > 0.05). The total pregnancy was 42.50% on first, 64.70% on second service and total delivery was 86.20% singletons, 12.06% twins and 3.33% triples with prolificacy of 1.15 ± 0.31. On both Semiarid and Zona da Mata regions, the majority of estrous events occurred between the11th and 15th day of the breeding season for Santa Inês ewes and between 6th and 10th day for Morada Nova ewes. Discussion: The occurrence of estrous, for both breeds, in both regions, were detected throughout the breeding seasons, despite most estrous detections were within the initial fifteen days, which normally happens with cycling pluriparous females, in disagreement with findings in the literature that young females display lower reproductive performance on the first breeding season. However, the sexual inexperience of young females is not equivalent to lack of male receptivity, since then, could not be responsible for late estrous onset in a breeding season of young females. In agreement with this statement, and based on the data described here, it has been described that young ewes display estrous within the initial 18 days of breeding season onset. The estrous dispersion in biostimulation programs is normally due to female cyclicity, a physiological condition that lowers the sensibility to estradiol negative feedback response, but are still responsible to the presence of males.